Pengaruh Latihan Menggunakan Target Cone Bervariatif Terhadap Akurasi Passing Pemain Sepak Bola SSB CISC Kendari U-13 - Hairil, Fitriani, Basman (Jurnal Ilmu Sosial Dan Pendidikan, 2024)
Passing is moving the ball from one player to another. In training passing we must concentrate so that the ball we pass remains straight and in the desired direction. For this reason, a study was conducted on the effect of training using variative target cones on the passing accuracy of football players SSB CISC Kendari U-13 with three experiments in one week, namely Wednesday, Friday and Sunday. This study was conducted to determine the effect of target passing training and training using variative target cones. To achieve this target, four models of target passing exercises and four exercises using variative cones were carried out. Based on the research that has been conducted, before the training using variative target cones on the passing accuracy of football players SSB CISC Kendari U-13, it can be seen that the average value (Pre-Test) = 4,8 which is very low. However, after the researcher carried out the treatment, namely training using variative target cones on the passing accuracy of football players SSB CISC Kendari U-13, the average value (Post-Test) = 6,95. Based on these values, it can be seen that there is a significant increase so that it is very effective if used. Based on the Hypothesis Test using the Paired Samples Test that t count (5,804)> t table (1,73961) and sig value (0,001 < 0,05), then H0 is rejected and Ha is accepted, it can be concluded that there is a difference before and after doing target passing exercises and exercises using variative cones on the passing accuracy of football players SSB CISC Kendari U-13.